PENGGUNAAN FUZZY LOGIC CONTROLLER PADA FILTER AKTIF UNTUK MEREDAM HARMONISA AKIBAT BEBAN NON LINIER DI BALI NATIONAL GOLF RESORT - Bagus Kurniawan; I Wayan Arta Wijaya; I Wayan Rinas (Jurnal SPEKTRUM, 2020)
The type of load contained in the electrical system at Bali National Golf Resort is a nonlinier load. on-linear loads, it can cause harmonics and make a decrease in quality of electricpower. Harmonics can be bad impact for the sinusoidal shape of current and voltage waves andthen making the electrical system abnormal. To reduce harmonics we need the addition of anactive filter. This research will focus on simulating the use of Fuzzy Logic Controller on activefilters to reduce harmonics. The simulation is done using MATLAB R2013 software. As theresults, The usage of Fuzzy Logic Controller on active filter are able to reduce the harmonicswhere the current and voltage harmonic values fall, average to 0,86% and 0,11%.